Gut Microbiota and Energy Expenditure in Health and Obesity. (November 2015) - Bakker, Guido J.; Zhao, Jing; Herrema, Hilde; Nieuwdorp, Max
Abstract : The contribution of intestinal bacterial strains (gut microbiota) to the development of obesity and obesity-related disorders is increasingly recognized as a potential diagnostic and pharmacologic target. Alterations in the intestinal bacterial composition have been associated with presence of chronic low-grade inflammation, a known feature of insulin resistance and type 2 diabetes mellitus. However, causality still needs to be proven. Fecal transplantation studies in germ-free mice have provided crucial insight into the causality of gut microbiota in development of obesity and obesity-related disorders. Moreover, fecal transplantation studies in conjunction with fecal sampling in prospectively followed cohorts will help identify causally involved intestinal bacterial strains in human obesity. Results from these studies will lead to characterization of novel diagnostic markers as well as therapeutic strategies that aim to treat obesity and obesity-related disorders.